Supervised feature selection using principal component analysis - Rahmat, Fariq; Zulkafli, Zed; Ishak, Asnor Juraiza; Abdul Rahman, Ribhan Zafira; Stercke, Simon De; Buytaert, Wouter; Tahir, Wardah; Ab Rahman, Jamalludin; Ibrahim, Salwa; Ismail, Muhamad (Springer Science and Business Media Deutschland GmbH, 2023)
The principal component analysis (PCA) is widely used in computational science branches such as computer science, pattern recognition, and machine learning, as it can effectively reduce the dimensionality of high-dimensional data. In particular, it is a popular transformation method used for feature extraction. In this study, we explore PCA’s ability for feature selection in regression applications. We introduce a new approach using PCA, called Targeted PCA to analyze a multivariate dataset that includes the dependent variable—it identifies the principal component with a high representation of the dependent variable and then examines the selected principal component to capture and rank the contribution of the non-dependent variables. The study also compares the feature selected with that resulting from a Least Absolute Shrinkage and Selection Operator (LASSO) regression. Finally, the selected features were tested in two regression models: multiple linear regression (MLR) and artificial neural network (ANN). The results are presented for three socioeconomic, environmental, and computer image processing datasets. Our study found that 2 of 3 random datasets have more than 50% similarity in the selected features by the PCA and LASSO regression methods. In the regression predictions, our PCA-selected features resulted in little difference compared to the LASSO regression-selected features in terms of the MLR prediction accuracy. However, the ANN regression demonstrated a faster convergence and a higher reduction of error. © The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2023.